Chemistry - Overby, Jason; Chang, Raymond (McGraw Hill LLC, 2022)
Chemistry, 14th Edition, continues a long-standing tradition of providing a firm foundation in the concepts of chemical principles while instilling an appreciation for the important role chemistry plays in our daily lives. This text provides a balance of theory and application, while illustrating the principles with applicable examples.